Cu-Fe alloy material with high strength, high conductivity and high heat resistance and preparation method of Cu-Fe alloy material
By adding trace elements to Cu-Fe alloy and adopting electrical pulse treatment and water quenching processes, the problem of softening Cu-Fe-P alloy in high-temperature environments is solved, and a balance between high strength, high conductivity and high heat resistance is achieved. It is suitable for high-performance electrical materials and high-temperature resistant applications.
Patent Information
- Application Number
- CN202411920259.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-25
- Publication Date
- 2025-03-21
- Estimated Expiration
- 2044-12-25
AI Technical Summary
The existing Cu-Fe-P alloy materials soften in high-temperature service environments, resulting in damage to the circuit. The traditional solid solution treatment has problems such as high energy consumption, difficulty in removing surface oxide layers, and abnormal growth of grains, which affect performance.
A Cu-Fe alloy with low Fe content is used, and by adding trace elements such as Mg, Si, V, P, Nb, etc., electrical pulse treatment and water quenching process are used to form a multi-scale heat-resistant second phase and refined grains to enhance the work hardening effect.
The balance between high strength, high conductivity and high heat resistance of Cu-Fe alloy is achieved, and the thermal stability, softening resistance and comprehensive performance of the material are improved. It is suitable for high-performance electrical materials and high-temperature resistant applications.
Smart Images

Figure CN119663044A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of new copper alloy materials, and in particular relates to a Cu-Fe alloy material having high strength, high conductivity and high heat resistance and a preparation method thereof. Background Art
[0002] Cu-Fe-P alloy has good strength and electrical conductivity. Due to its low cost and good processing performance, it is currently the mainstream material used in integrated circuit lead frames. As a key structural component of semiconductor packaging, the lead frame material needs to ensure the rapid and lossless transmission of electrical signals, withstand various stresses during packaging and use without breaking easily, and be able to effectively transfer and withstand the heat generated when the chip is working to prevent overheating failure. This requires not only that the material has high electrical conductivity and strength, but also excellent resistance to high temperature softening. At present, the common Cu-Fe-P lead frame material has a conductivity of more than 60% IACS, a hardness of 120~150 HV, and a softening temperature of 400~500℃. In more complex and harsh high-temperature service environments, such as aerospace, nuclear industry, etc., the softening of the material will make it unable to effectively support the normal operation of the chip, thereby causing damage to the circuit.
[0003] At present, the preparation of heat-treatable and strengthened non-ferrous metal materials mostly adopts the process of "ingot → hot rolling → processing → aging". However, traditional solution treatment requires long-term annealing at high temperature (about 0.9Ts, Ts is the melting point of the alloy), which has high energy consumption and is easy to form a difficult-to-remove surface oxide layer, affecting product quality. In addition, solution treatment is prone to abnormal grain growth and uneven size distribution, resulting in uneven organization and decreased mechanical properties; the coarse and uneven copper matrix grains after solution treatment will aggravate the uneven deformation during cold rolling, resulting in residual stress concentration, poor surface quality, low dimensional accuracy, and even cracks or fractures. Therefore, the current preparation process of Cu-Fe-P alloys often abandons the solution process, but this will also lead to poor uniformity of sheet composition, especially the strengthening effect of the second phase is greatly reduced, resulting in decreased stability of sheet performance. In addition, although aging treatment can precipitate strengthening phases, the organization is still elongated fibrous in the peak aging state, with severe anisotropy, especially low bending resistance and toughness, which makes it difficult to meet the requirements of deep processing and high safety. Summary of the invention
[0004] In view of the shortcomings of the prior art, the first object of the present invention is to provide a Cu-Fe alloy material with high strength, high conductivity and high heat resistance.
[0005] The second object of the present invention is to provide a method for preparing a Cu-Fe alloy material having high strength, high conductivity and high heat resistance.
[0006] In order to achieve the above object, the present invention adopts the following technical solution: The present invention provides a Cu-Fe alloy material with high strength, high conductivity and high heat resistance. The Cu-Fe alloy material has the following components, measured by mass percentage: Fe: 0.8-3%, Mg: 0.05-0.2%, Si: 0-0.1%, Nb: 0-0.2%, V: 0-0.1%, P: 0-0.1%, and the balance is Cu. Meanwhile, the total mass percentage of Si, V, P and Nb is less than 0.2%.
[0007] The present invention uses a lower content of Fe element than in the prior art, which can greatly reduce the scattering effect of impurity atoms on electrons, is more conducive to improving the conductivity of Cu-Fe alloys, and promotes the application of Cu-Fe alloys in the fields of electronic information, transportation, etc. On the other hand, since the main strengthening effect of Cu-Fe alloys with lower Fe content comes from work hardening, the α-Fe phase precipitated by aging will coarsen rapidly at high temperature, weakening the interaction between the dislocation substructure generated by processing and the precipitated phase, thereby greatly reducing the strength and heat resistance of the alloy; based on this, the present invention, on the one hand, adds Mg element, and utilizes Mg element to effectively delay the precipitation phase transformation of α-Fe phase, inhibit the rapid coarsening of α-Fe phase at high temperature, and at the same time, Mg element itself can form stable magnesium compounds under high temperature conditions, thereby improving the thermal stability and softening resistance of the material; on the other hand, by adding trace elements Si, V, P, Nb, they can form heat-resistant primary second phases with Fe phase, such as Fe3Si, Fe3P, etc., and by adding more trace elements, multi-scale heat-resistant second phases are formed in Cu-Fe alloys, and appropriate amounts of trace elements can further refine the grains, inhibit grain growth, and improve the mechanical properties of the material, thereby synergistically enhancing the work hardening effect to form a high-strength, high-conductivity, heat-resistant Cu-Fe alloy under the synergistic effect of multiple strengthening mechanisms.
[0008] However, it can be seen that in the composition of the present invention, the total content of alloy elements is strictly controlled within a reasonable range, especially the total mass percentage of elements with relatively sensitive conductivity (such as Si, V, P, Nb) is limited to <0.2%. In this way, the strength can be improved while the influence on the conductivity of the copper matrix can be reduced as much as possible, ensuring that the alloy has high conductivity and avoiding brittleness or other negative effects caused by excessive impurity elements, so that the alloy has excellent ductility and comprehensive performance while maintaining high strength and heat resistance.
[0009] The present invention successfully achieves a balance between the high strength, high conductivity and heat resistance of the Cu-Fe alloy material, making the Cu-Fe alloy suitable for high-performance electrical materials and high-temperature resistant application scenarios.
[0010] In a preferred embodiment, the Cu-Fe alloy material has the following composition, in mass percentage: Fe: 1.5-3%, Mg: 0.05-0.15%, Si: 0-0.05%, Nb: 0-0.05%, V: 0-0.05%, P: 0-0.05%, and the balance is Cu.
[0011] Further preferably, the Cu-Fe alloy material has the following composition, in mass percentage: Fe: 2.0-2.3%, Mg: 0.08-0.1%, Si: 0.01-0.03%, Nb: 0.01-0.02%, V: 0.01-0.03%, P: 0.03-0.04%, and the balance is Cu.
[0012] The invention provides a preparation method of a Cu-Fe alloy material with high strength, high conductivity and high heat resistance. The method comprises the following steps: obtaining an ingot by smelting, subjecting the ingot to a first electric pulse treatment, then hot rolling, subjecting the ingot to a second electric pulse treatment after hot rolling, subjecting the ingot to a first cold rolling treatment, a third electric pulse treatment, a second cold rolling treatment, and subjecting the Cu-Fe alloy material to a fourth electric pulse treatment. The cooling method after the first electric pulse treatment, hot rolling and the second electric pulse treatment is water quenching.
[0013] Since the Cu-Fe alloy material of the present invention adopts a lower Fe content, the main source of strengthening is work hardening. Work hardening is a strengthening mechanism that introduces a large number of dislocations through plastic deformation, thereby improving the strength of the material; the preparation method of the present invention utilizes the rapid processing effect of electric pulses, combined with a water quenching process, to quickly fix the work-hardened organizational state, so that the dislocation density and organizational distortion state can be retained. Its benefits mainly include: (1) improving the strength and hardness of the alloy and significantly enhancing the ability to resist plastic deformation; (2) providing a high-strength foundation in the processing state, which is convenient for performance optimization in subsequent applications; (3) improving wear resistance and fatigue resistance, making the alloy more suitable for use under complex working conditions.
[0014] The present invention forms a preparation process that is significantly different from the prior art by combining full-process electric pulse treatment with water quenching and composition optimization. On the one hand, this method retains the work hardening effect and improves the strength and hardness; on the other hand, by introducing Mg and other trace elements and regulating Fe precipitation, the distribution of the strengthening phase is optimized, avoiding the coarsening problem in the traditional process, thereby achieving efficient, energy-saving and excellent performance Cu-Fe alloy preparation.
[0015] In the present invention, the first two electric pulse treatments can fully dissolve the Fe element in the Cu matrix before cold rolling, and can make the trace elements such as Mg, Si, V, P, and Nb more evenly distributed in the Cu matrix. During the third and fourth electric pulse treatments, high energy input will stimulate more α-Fe phase precipitation sites, so that the α-Fe phase can be more dispersed and fully precipitated. At this time, the more evenly distributed Mg, Si, V, P, and Nb elements can more fully interact with these α-Fe phases, thereby better inhibiting the high-temperature coarsening of the α-Fe phase.
[0016] In addition, during the electric pulse treatment process, due to the instantaneous high energy input, a significant thermal vibration effect will occur inside the material, and the grains may grow rapidly under high temperature conditions. Rapid cooling achieved through water quenching can effectively freeze the migration behavior of the grain boundaries, inhibit grain growth, and control the final grain size well, thereby improving the strength and toughness of the material and locking the non-equilibrium structure. During the electric pulse treatment process, the Cu matrix and Fe elements in the alloy will be in a non-equilibrium dissolution or precipitation state. Water quenching can quickly "fix" this organizational state, providing an ideal initial organizational foundation for the final precipitation and reducing internal stress and segregation.
[0017] Preferably, the smelting is non-vacuum smelting.
[0018] The preferred solution is that the smelting process is as follows: pure copper, Cu-Fe master alloy, Cu-V master alloy, Cu-Nb master alloy, pure Si, pure Mg, and pure P are prepared according to the designed proportion, pure copper is melted first, and then the temperature is raised to 1200-1300°C, Cu-Fe master alloy is added in 2-3 batches, and the mixture is kept warm for 2-3 minutes and stirred for 30-60 seconds, and then Cu-V master alloy, Cu-Nb master alloy, pure Si, pure Mg, and pure P are added, and the mixture is kept warm for 1-2 minutes, and then the mixture is cooled to 1150-1250°C while stirring, and then cast. By the above-mentioned feeding method, the alloy liquid obtained by smelting can be made the most uniform.
[0019] In a preferred embodiment, the parameters of the first electric pulse treatment are: frequency of 3000-5000 Hz, pulse width of 500-3000 μs, and current density of 4000-8000 A / mm 2 , effective current density is 550~2500 A / mm 2 The maximum temperature of the first electric pulse treatment is 750-950℃, and the time of the first electric pulse treatment is 2-5 minutes. In the actual operation process, the surface defects of the ingot are removed and corrected by machining after the first electric pulse treatment to ensure that there is no oxide layer, shrinkage hole and inner hole on the surface of the ingot.
[0020] After obtaining the ingot, the present invention performs a short first electric pulse treatment on the ingot, and accelerates the diffusion process of the Fe element in the Cu matrix through the instantaneous high energy input and rapid heating effect of the electric pulse, and quickly eliminates the element segregation. At the same time, the electric field effect of the electric pulse can reduce the element concentration gradient near the grain boundary, promote the uniform distribution of the alloy components, eliminate local defects and internal stresses in the cast structure, improve the overall structural uniformity of the alloy, and avoid the phenomenon of grain coarsening.
[0021] In a preferred embodiment, the hot rolling process is to first keep the temperature at 850-950°C for 0.5-1 h and then perform hot rolling, wherein the deformation of a single pass of hot rolling is controlled to be 20-40%, preferably 35-40%, the total deformation is 50-90%, and the total number of passes is ≤3.
[0022] In the present invention, by controlling the total number of passes to ≤3, that is, using a larger reduction amount in a single-pass processing, dislocations and distortion structures can be introduced into the material to a greater extent, thereby increasing the density of the material and improving the work hardening effect as much as possible. After subsequent hot rolling, the material is immediately water quenched to retain the work hardening effect.
[0023] In addition, controlling the amount of reduction and the total number of passes within the scope of the present invention also has the following advantages: (1) Improving production efficiency: reducing the number of passes, shortening processing time, reducing equipment wear and energy consumption, and thus significantly reducing manufacturing costs. (2) Reducing the thermal accumulation effect of materials: reducing the risk of grain growth and oxidation loss, reducing the performance degradation of materials at high temperatures, and improving the yield rate. (3) Optimizing material properties: reducing the number of passes helps to improve the uniformity of the structure, reduce residual stress, and improve the strength, toughness and dimensional stability of the material. (4) Supporting advanced processes: combining technologies such as controlled rolling and controlled cooling, reducing the number of passes optimizes the process flow, improves product quality, and reduces the need for subsequent processing. (5) Energy saving and emission reduction: reducing the number of heating times can reduce energy consumption and carbon emissions, meeting the requirements of green manufacturing.
[0024] In a preferred embodiment, the thickness of the hot-rolled billet obtained after hot rolling is ≥10 mm. In the present invention, the thickness of the hot-rolled billet needs to be controlled to be above 10 mm. Too thin hot-rolled billet cannot provide sufficient deformation margin for subsequent rolling deformation and cannot further improve the work hardening effect.
[0025] In a preferred embodiment, the parameters of the second electric pulse treatment are: frequency of 2000-5000 Hz, pulse width of 500-3000 μs, and current density of 3000-8000 A / mm 2 , effective current density is 500~2000 A / mm 2The maximum temperature of the second electric pulse treatment is 700-900°C, and the time of the second electric pulse treatment is 20 s-5 min. The Cu-Fe alloy hot-rolled billet after the second electric pulse treatment is water quenched and then machined to remove the surface oxide layer.
[0026] The second electric pulse treatment further dissolves the Fe element quickly and fully in the Cu matrix, and makes the trace elements Mg, Si, V, P, and Nb more evenly distributed in the Cu matrix. Compared with traditional heat treatment, the electric pulse treatment adopted in the present invention can be carried out at a lower temperature, reducing the adverse effects of high-temperature treatment on the microstructure of the alloy. The second electric pulse treatment is used for rapid heating and cooling, which ensures that the Fe element is fully dissolved, inhibits grain growth, maintains the fine grain structure of the matrix, and further improves the comprehensive performance of the alloy.
[0027] In a preferred embodiment, the deformation amount of a single cold rolling pass is 10-20%, the total deformation amount is 50-90%, and the number of passes is ≤6.
[0028] In a preferred embodiment, the thickness of the blank obtained after the first cold rolling is ≥1 mm. If the thickness after the first cold rolling is controlled within this range, sufficient deformation margin can be further provided for the second cold rolling, thereby improving the work hardening effect.
[0029] In a preferred embodiment, the parameters of the third electric pulse treatment are: frequency of 2000-5000 Hz, pulse width of 500-3000 μs, and current density of 1500-5000 A / mm 2 , effective current density is 500~1500 A / mm 2 ; The temperature of the third electric pulse treatment is 550-650°C, and the time of the third electric pulse treatment is 20s-60s.
[0030] In a preferred embodiment, the deformation amount of a single pass of the secondary cold rolling is 10-15%, the total deformation amount is 50-90%, and the total number of passes is ≤7.
[0031] In a preferred embodiment, the parameters of the fourth electric pulse treatment are: frequency of 2000-4000 Hz, pulse width of 500-3000 μs, and current density of 1500-4000 A / mm 2 , effective current density is 500~1200 A / mm 2 ; The temperature range of the fourth electric pulse treatment is 400-500°C, and the time of the fourth electric pulse treatment is 20 s-60 s.
[0032] Due to the short treatment time and the low degree of surface oxidation, a clean surface can be obtained by pickling only.
[0033] In the present invention, after the first cold rolling and the second cold rolling, the third and fourth electric pulse treatments are respectively performed, and finally a fine and dispersed α-Fe phase is precipitated.
[0034] The inventors found that, since Mg and other microalloying elements are introduced in the present invention, only by the third and fourth electric pulse treatments can a finely dispersed α-Fe phase be obtained, which cannot be obtained by conventional heat treatment. The main reasons are as follows: 1. Synergistic effect of dynamic grain boundary movement and strengthening phase refinement The instantaneous high temperature and electric field effect in the electric pulse treatment will induce dynamic grain boundary movement. This grain boundary migration can be achieved at a relatively low temperature, which helps to refine the grains and avoid excessive coarsening of the Fe phase at the grain boundaries. After the introduction of microalloying elements such as Mg, the microalloying atoms tend to be concentrated at the grain boundaries, further enhancing the inhibitory effect on grain boundary movement, thereby inhibiting the coarsening of the Fe phase. This dynamic regulation effect cannot be achieved by traditional heat treatment.
[0035] 2. Activation and distribution adjustment of microalloying elements such as Mg induced by electric pulse The high-density current in the electric pulse treatment can activate the microalloying atoms and accelerate their diffusion and uniform distribution in the Cu matrix. The segregation of microalloying inhibits the enrichment of Fe elements at grain boundaries and subgrain boundaries, effectively limiting the growth and coarsening of the Fe phase in subsequent treatment. In traditional heat treatment, the diffusion rate of microalloying atoms is slow, and similar effects cannot be achieved in a short time.
[0036] 3. Morphology Control of Precipitation Phase The electric pulse treatment changes the precipitation path of the Fe phase through "instantaneous hot-cold cycles". In the third and fourth electric pulse treatments, the precipitation of the strengthening phase tends to exist in the form of fine particles or dispersed precipitation, rather than growing into sheets or forming coarse dendritic Fe phases. After the introduction of microalloying atoms such as Mg, the atoms further reduce the surface energy of the strengthening phase by forming a metastable composite phase with Fe, inhibit the coarsening of the Fe phase, and promote the uniform distribution of precipitated particles. Traditional heat treatment often lacks such precipitation morphology control capabilities.
[0037] 4. Electric field effect and diffusion barrier reduction The electric field effect of the electric pulse reduces the diffusion barrier of Fe atoms and accelerates the movement of Fe elements in the Cu matrix. At the same time, the electric pulse enhances the interaction between microalloying atoms and Fe, enabling them to participate in regulating the precipitation process of Fe more effectively. This effect is particularly obvious after repeated cold rolling-electric pulse treatment, because the high-density dislocations generated by cold rolling provide channels for the diffusion of microalloying atoms such as Mg and Fe atoms, and the electric pulse further activates the diffusion process. This effect is difficult to achieve in traditional heat treatment because traditional heat treatment is limited by the thermal diffusion mechanism and has a slow rate.
[0038] Principles and advantages The present invention provides a Cu-Fe alloy material having high strength, high conductivity and high heat resistance. The present invention adopts a lower content of Fe element than that in the prior art, which can greatly reduce the scattering effect of impurity atoms on electrons, and is more conducive to improving the conductivity of the Cu-Fe alloy, thereby promoting the application of the Cu-Fe alloy in the fields of electronic information, transportation and the like. On the other hand, since the main strengthening effect of Cu-Fe alloys with lower Fe content comes from work hardening, the α-Fe phase precipitated by aging will coarsen rapidly at high temperature, weakening the interaction between the dislocation substructure generated by processing and the precipitated phase, thereby greatly reducing the strength and heat resistance of the alloy; based on this, the present invention, on the one hand, adds Mg element, and utilizes Mg element to effectively delay the precipitation phase transformation of α-Fe phase, inhibit the rapid coarsening of α-Fe phase at high temperature, and at the same time, Mg element itself can form stable magnesium compounds under high temperature conditions, thereby improving the thermal stability and softening resistance of the material; on the other hand, by adding trace elements Si, V, P, Nb, they can form heat-resistant primary second phases with Fe phase, such as Fe3Si, Fe3P, etc., and by adding more trace elements, multi-scale heat-resistant second phases are formed in Cu-Fe alloys, and appropriate amounts of trace elements can further refine the grains, inhibit grain growth, and improve the mechanical properties of the material, thereby synergistically enhancing the work hardening effect to form a high-strength, high-conductivity, heat-resistant Cu-Fe alloy under the action of multiple strengthening mechanisms.
[0039] The preparation method provided by the present invention utilizes the rapid processing effect of electric pulses and combines it with a water quenching process to quickly fix the work-hardened organizational state, so that the dislocation density and organizational distortion state can be retained. Its benefits mainly include: (1) improving the strength and hardness of the alloy and significantly enhancing the ability to resist plastic deformation; (2) providing a high-strength foundation in the processing state, which is convenient for performance optimization in subsequent applications; (3) improving wear resistance and fatigue resistance, making the alloy more suitable for use under complex working conditions.
[0040] In summary, the present invention achieves a comprehensive improvement in the performance of Cu-Fe alloys by combining alloy composition optimization, full electric pulse treatment during the preparation process, and water quenching treatment. The present invention not only improves the strength, toughness, and high-temperature stability of the alloy, but also improves the uniformity and softening resistance of the organization. The preparation cycle is short, the electric pulse treatment time is short, and it is highly efficient, providing an efficient, energy-saving, and adjustable innovative solution for the research and development of high-performance copper-based alloys. BRIEF DESCRIPTION OF THE DRAWINGS
[0041] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the following briefly introduces the drawings required for describing the embodiments. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative labor. Among them: Figure 1 This is a photo of a solid solution ingot of a high-strength, high-conductivity and high-heat-resistant Cu-Fe alloy material prepared in Example 1 of the present invention after machining to remove the oxide layer.
[0042] Figure 2 This is the finished product obtained by pickling after secondary aging in the alloy preparation process of Example 1 of the present invention.
[0043] Figure 3 This is the TEM observation after high-energy electric pulse aging during the preparation process of Example 1 of the present invention.
[0044] Figure 4 This is the TEM observation after high-energy electric pulse aging during the preparation process of the alloy of Comparative Example 1 of the present invention.
[0045] Figure 5 This is the metallographic structure after high-energy electric pulse solution treatment during the preparation process of the alloy in Example 2 of the present invention.
[0046] Figure 6 This is the metallographic structure after high-energy electric pulse intermediate annealing treatment during the preparation process of the alloy in Example 2 of the present invention.
[0047] Figure 7 This is the metallographic structure of the alloy after solution treatment in a heating furnace during the preparation process of comparative example 4 of the present invention.
[0048] Figure 8 This is the metallographic structure after intermediate annealing in a heating furnace during the preparation of the alloy of comparative example 5 of the present invention.
[0049] Fig. 9 This is the metallographic structure of the alloy after high-energy electric pulse intermediate annealing treatment during the preparation process of comparative example 6 of the present invention. DETAILED DESCRIPTION
[0050] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, the specific implementation methods of the present invention are described in detail below in conjunction with the embodiments of the specification.
[0051] In the following description, many specific details are set forth to facilitate a full understanding of the present invention, but the present invention may also be implemented in other ways different from those described herein, and those skilled in the art may make similar generalizations without violating the connotation of the present invention. Therefore, the present invention is not limited to the specific embodiments disclosed below.
[0052] Secondly, the term "one embodiment" or "embodiment" as used herein refers to a specific feature, structure, or characteristic that may be included in at least one implementation of the present invention. The term "in one embodiment" that appears in different places in this specification does not necessarily refer to the same embodiment, nor does it refer to a separate or selective embodiment that is mutually exclusive with other embodiments.
[0053] Example 1
[0054] Example 1: A Cu-Fe alloy material with high strength, high conductivity and high heat resistance is prepared. In terms of mass percentage, the material components include Fe: 2.3%, Mg: 0.1%, P: 0.03%, Si: 0.03%, Nb: 0.01%, V: 0.01%, and the balance is Cu.
[0055] The preparation method of the high-strength, high-conductivity and high-heat-resistant Cu-Fe alloy material selected in Example 1 comprises the following steps: Step (1): Use a medium frequency induction melting furnace for non-vacuum melting to obtain an ingot. The raw materials added for melting include electrolytic copper (99.95wt.%), Cu-10wt.%Fe master alloy, Cu-5wt.%V master alloy, Cu-5wt.%Nb master alloy, pure Si (99.95wt.%), pure Mg (99.95wt.%), and pure P (99.95wt.%). Before melting, the raw materials, crucible, and mold are dried. In the melting process, pure copper is first melted (1083°C), and the Cu-Fe master alloy is added at a melt temperature of 1250°C, and is added in three batches. After keeping warm for 2.5 minutes, stir for 45 seconds; then add Cu-Nb master alloy, Cu-V master alloy, pure Si, pure Mg, and pure P. After keeping warm for 1.5 minutes, stir and reduce the power of the induction furnace while reducing the melt temperature to 1200°C and start casting.
[0056] Step (2) The ingot is subjected to the first electric pulse treatment. The parameters input to the Cu-Fe alloy cold-rolled strip electrification zone during the high-energy electric pulse aging treatment are: frequency of 3000 Hz, pulse width of 1000 μs, and current density of 7000 A / mm 2, effective current density is 2000 A / mm 2 The temperature of the first electric pulse treatment is 920℃, the time of the first electric pulse treatment is 4 min, and the ingot is water quenched after the first electric pulse treatment, and then the surface defects of the ingot are removed and corrected by machining to ensure that there is no oxide layer, shrinkage hole and inner hole on the surface of the ingot.
[0057] Step (3) hot rolling blanking treatment, the holding temperature before hot rolling is 900°C, the holding time is 0.5 h, the single hot rolling reduction is about 40%, the cumulative hot rolling deformation is about 80%, the hot rolling is completed in 2 passes, the hot rolling is followed by water quenching, and the surface oxide layer is removed by machining. The thickness of the hot rolled blank is about 16.5 mm.
[0058] Step (4) The ingot is subjected to a second electric pulse treatment. The parameters input to the Cu-Fe alloy hot-rolled billet power-on zone during the second electric pulse treatment are: frequency of 3000 Hz, pulse width of 2000 μs, and current density of 6500 A / mm 2 , effective current density is 1800 A / mm 2 ; The maximum temperature of the second electric pulse treatment is 850℃, and the time of the second electric pulse treatment is 4 min; The Cu-Fe alloy hot-rolled billet after the second electric pulse treatment is water quenched.
[0059] In step (5), the strip after the second electric pulse treatment is subjected to a cold rolling. The single deformation amount of the cold rolling is 15-20%, the cumulative total deformation amount is about 90%, and the cold rolling is completed in 5 passes. The thickness of the strip after the cold rolling is about 1.6 mm.
[0060] Step (6) The strip after the first cold rolling is subjected to a third electric pulse treatment. The parameters input to the power-on region of the Cu-Fe alloy cold-rolled strip during the third electric pulse treatment are: frequency of 3500 Hz, pulse width of 2000 μs, and current density of 3000 A / mm 2 , effective current density is 1000 A / mm 2 ; The temperature of the third electric pulse treatment is 600℃, and the time of the third electric pulse treatment is 40 s.
[0061] Step (7) performs secondary cold rolling on the strip after the third electric pulse treatment. The single deformation of the secondary cold rolling is about 10-15%, the cumulative total deformation is about 88%, and the secondary cold rolling is completed in 6 passes. The thickness of the strip after cold rolling is about 0.2 mm.
[0062] Step (8) performs a fourth electric pulse treatment on the strip after the secondary cold rolling. The parameters input to the power-on region of the Cu-Fe alloy cold-rolled strip during the fourth electric pulse treatment are: frequency of 3000 Hz, pulse width of 2500 μs, and current density of 2500 A / mm 2 , effective current density is 800 A / mm 2 The temperature of the fourth electric pulse treatment is 450°C, the time of the fourth electric pulse treatment is 40 s, and then the finished product with a clean surface is obtained by pickling.
[0063] Comparative Example 1 Comparative Example 1: A Cu-Fe alloy material was prepared. In terms of mass percentage, the material components included Fe: 2.3%, Mg: 0.02%, P: 0.03%, Si: 0.03%, Nb: 0.01%, V: 0.01%, and the balance was Cu.
[0064] The subsequent preparation process is the same as that in Example 1.
[0065] Figure 5 This is the TEM observation result after the fourth electric pulse treatment during the preparation process of the alloy in comparative example 1.
[0066] Comparative Example 2 Comparative Example 2: A Cu-Fe alloy material was prepared. In terms of mass percentage, the material components included Fe: 2.3%, Mg: 0.15%, P: 0.03%, Si: 0.4%, Nb: 0.01%, V: 0.01%, and the balance was Cu.
[0067] The subsequent preparation process is the same as that in Example 1.
[0068] Comparative Example 3 Comparative Example 3: A Cu-Fe alloy material was prepared. In terms of mass percentage, the material components included Fe: 2.3%, Mg: 0.15%, P: 0.03%, Si: 0.05%, Nb: 0.8%, V: 0.01%, and the balance was Cu.
[0069] The subsequent preparation process is the same as that in Example 1.
[0070] Table 1 is a comparison of the properties of Cu-Fe alloys in the solid solution state and after treatment with Example 1, Comparative Example 1, Comparative Example 2, and Comparative Example 3. The Cu-Fe alloy treated with the process of Example 1 obtained the highest hardness and tensile strength among all samples. Although the elongation and conductivity of Comparative Example 1 are better than those of Example 1, the hardness, tensile strength and softening temperature of Comparative Example 1 are much lower than those of Example 1, and it does not belong to the category of high-strength and high-heat-resistant alloys. In addition, due to excessive addition of elements, although Comparative Examples 2 and Comparative Examples 3 are comparable to Example 1 in terms of hardness, tensile strength and softening temperature, their elongation and conductivity are greatly reduced, and the overall performance is still not as good as Example 1.
[0071]
[0072] Figure 1 This is a photo of a solid solution ingot of a high-strength, high-conductivity and high-heat-resistant Cu-Fe alloy material prepared in Example 1 of the present invention after machining to remove the oxide layer.
[0073] Figure 2 This is the finished product obtained by pickling after the fourth electric pulse treatment in the alloy preparation process of Example 1 of the present invention.
[0074] Figure 3 This is the TEM observation result after high-energy electric pulse aging in the preparation process of the alloy of Example 1 of the present invention. The size and distribution of the α-Fe phase as the main strengthening precipitation phase in the alloy are statistically analyzed here. The phenomenon of subgrain boundaries formed by dislocation walls connecting and merging can be observed in the selected area. When the subgrain boundaries migrate here, they will definitely be pinned by the α-Fe phase. It can be seen that the second phase in the finished state is finely dispersed, and the average size of the second phase is 20.68 nm, which effectively hinders the migration of dislocations and grain boundaries during the softening process of the material.
[0075] Figure 4 This is the TEM observation result after the fourth electric pulse treatment in the preparation process of the alloy of the present invention's comparative example 1. In the same selected area, it can be observed that the dislocation walls are connected and merged to form subgrain boundaries. Figure 3 and Figure 4 The comparison directly shows the difference in the size and distribution of the α-Fe phase of the two alloys during the grain boundary formation process. Compared with Example 1, the size of the second phase in Comparative Example 1 is significantly coarser, and the density of the phase distribution is not as good as that in Example 1. Due to the appropriate addition of the Mg element, the α-Fe phase of the Cu-Fe alloy of Example 1 can maintain a finer and more dispersed distribution state at high temperatures, which is beneficial for resisting the softening caused by recrystallization of the copper matrix and improving the alloy's resistance to high-temperature softening. It can also retain more work hardening effects during the aging process and improve its strength.
[0076] Example 2 Example 2: A Cu-Fe alloy material with high strength, high conductivity and high heat resistance is prepared. In terms of mass percentage, the material components include Fe: 2.0%, Mg: 0.08%, P: 0.03%, Si: 0.01%, Nb: 0.01%, V: 0.03%, and the balance is Cu.
[0077] The preparation method of the high-strength, high-conductivity and high-heat-resistant Cu-Fe alloy material selected in Example 2 comprises the following steps: Step (1): Use a medium frequency induction melting furnace for non-vacuum melting to obtain an ingot. The raw materials added for melting include electrolytic copper (99.95wt.%), Cu-10wt.%Fe master alloy, Cu-5wt.%V master alloy, Cu-5wt.%Nb master alloy, pure Si (99.95wt.%), pure Mg (99.95wt.%), and pure P (99.95wt.%). The raw materials, crucible, and mold are dried before melting. In the melting process, pure copper is first melted (1083°C), and the Cu-Fe master alloy is added at a melt temperature of 1270°C, and is added in two batches. After keeping warm for 2.5 minutes, stirring is performed; then, Cu-Nb master alloy, Cu-V master alloy, pure Si, pure Mg, and pure P are added. After keeping warm for 1.5 minutes, stirring is continued while reducing the power of the induction furnace (the process lasts for 60 seconds), so that the melt temperature is reduced to 1200°C and casting begins.
[0078] Step (2) performs the first electric pulse treatment on the ingot. The parameters input to the Cu-Fe alloy cold-rolled strip electrification zone during the first electric pulse treatment are: frequency of 4000 Hz, pulse width of 1500 μs, and current density of 6000 A / mm 2 , effective current density is 1800 A / mm 2 The temperature of the first electric pulse treatment is 910℃, the time of the first electric pulse treatment is 3 min, and the ingot is water quenched after the first electric pulse treatment, and then the surface defects of the ingot are removed and corrected by machining to ensure that there is no oxide layer, shrinkage hole and inner hole on the surface of the ingot.
[0079] In step (3), the homogenized billet is subjected to hot rolling treatment. The holding temperature before hot rolling is 870° C., the holding time is 1 h, the single hot rolling reduction is about 35%, the cumulative hot rolling deformation is about 70%, the hot rolling is completed in 2 passes, the hot rolling is followed by water quenching, and the surface oxide layer is removed by machining. The thickness of the hot rolled billet is about 20.5 mm.
[0080] Step (4) The ingot is subjected to a second electric pulse treatment. The parameters input to the Cu-Fe alloy hot-rolled billet power-on zone during the second electric pulse treatment are: frequency of 3500 Hz, pulse width of 2500 μs, and current density of 6000 A / mm2 , effective current density is 1600 A / mm 2 The maximum temperature of the second electric pulse treatment was 830℃, and the time of the second electric pulse treatment was 3.5 min. The Cu-Fe alloy hot-rolled billet after the second electric pulse treatment was water quenched.
[0081] Step (5) cold rolling is performed on the strip after the second electric pulse treatment. The single deformation of the cold rolling is 15-20%, the cumulative total deformation is about 80%, and the cold rolling is completed in 4 passes. The thickness of the strip after the cold rolling is about 4.1 mm.
[0082] Step (6) The strip after the first cold rolling is subjected to a third electric pulse treatment. The parameters input to the power-on region of the Cu-Fe alloy cold-rolled strip during the third electric pulse treatment are: a frequency of 4000 Hz, a pulse width of 1000 μs, and a current density of 2500 A / mm 2 , effective current density is 900 A / mm 2 ; The temperature of the third electric pulse treatment is 580℃, and the time of the third electric pulse treatment is 30 s.
[0083] Step (7) performs secondary cold rolling on the strip after the third electric pulse treatment. The single deformation of the secondary cold rolling is about 10-15%, the cumulative total deformation is about 80%, and the secondary cold rolling is completed in 6 passes. The thickness of the strip after cold rolling is about 0.8 mm.
[0084] Step (8) performs a fourth electric pulse treatment on the strip after the secondary cold rolling. The parameters input to the power-on region of the Cu-Fe alloy cold-rolled strip during the fourth electric pulse treatment are: frequency of 2500 Hz, pulse width of 1500 μs, and current density of 3000 A / mm 2 , effective current density is 900 A / mm 2 The temperature of the fourth electric pulse treatment is 480°C, the time of the fourth electric pulse treatment is 30 s, and then the finished product with a clean surface is obtained by pickling.
[0085] Comparative Example 4 The Cu-Fe alloy material prepared in Comparative Example 4 has the same material components as those in Example 2.
[0086] The other preparation methods of the Cu-Fe alloy material selected in Comparative Example 4 are the same as those in Example 2, except that the second electric pulse blowing is replaced by a heating furnace treatment, the temperature is still 830° C., and the time is 60 min.
[0087] Comparative Example 5 The Cu-Fe alloy material prepared in Comparative Example 5 has the same material components as those in Example 2.
[0088] The other preparation methods of the Cu-Fe alloy material selected in Comparative Example 5 are the same as those in Example 2, except that the third electric pulse treatment is changed to a heating furnace treatment, the temperature is still 580° C., and the time is 60 min.
[0089] Comparative Example 6 The Cu-Fe alloy material prepared in Comparative Example 6 has the same material components as those in Example 2.
[0090] The other preparation methods of the Cu-Fe alloy material selected in Comparative Example 6 are the same as those in Example 2, except that the fourth electric pulse treatment is changed to a heating furnace treatment, the temperature is still 480° C., and the time is 60 min.
[0091] Comparative Example 7 The Cu-Fe alloy material prepared in Comparative Example 7 has the same material components as those in Example 2.
[0092] The other preparation methods of the Cu-Fe alloy material selected in Comparative Example 7 are the same as those in Example 2, except that the effective current density of the third electric pulse treatment is changed to 1600 A / mm 2 , at this time the alloy surface temperature is 820℃.
[0093] Comparative Example 8 The other conditions were the same as those in Example 2, except that the hot rolling was followed by air cooling.
[0094] Table 1 is a comparison of the properties of Cu-Fe alloys in the solid solution state and after treatment with Example 2, Comparative Example 4, Comparative Example 5, Comparative Example 6, and Comparative Example 7. The Cu-Fe alloy treated with the process of Example 2 has the highest hardness, tensile strength, and softening temperature among all samples. Although the elongation and conductivity of some comparative examples are better than those of Example 2, the hardness, tensile strength, and softening temperature of these comparative examples are reduced to varying degrees, and are far lower than those of Example 2, and do not belong to the category of high-strength and high-heat-resistant alloys.
[0095]
[0096] Figure 5 This is the metallographic structure after the second electric pulse treatment in the preparation process of the alloy of Example 2 of the present invention. It can be seen that even after the electric pulse treatment at a higher temperature, the grain size of the alloy under the process of Example 2 is not coarse, and the average grain size is 20.6 μm, which provides excellent initial organizational conditions for subsequent processing.
[0097] Figure 6This is the metallographic structure after the third electric pulse treatment in the preparation process of the alloy of Example 2 of the present invention. The picture shows that the alloy matrix grains after intermediate annealing are very fine and uniform, with an average grain size of 8.6 μm, maintaining the fine grain structure of the matrix and further improving the comprehensive performance of the alloy.
[0098] Figure 7 This is the metallographic structure after heat treatment in the heating furnace during the preparation of the alloy of comparative example 4 of the present invention. It can be seen that due to the long time required to complete the solid solution under the process of comparative example 4, the alloy grain size is very coarse, the average grain size is 59.7 μm, and the hot rolling structure is basically completely eliminated.
[0099] Figure 8 This is the metallographic structure of the alloy after heating furnace treatment during the preparation process of comparative example 5 of the present invention. It can be seen that the alloy has reached a completely recrystallized state at this time, but due to the long treatment time, the grains have grown, and the average grain size is about 18.3 μm. The coarsened intermediate annealing grains reduce the overall performance of the alloy and eliminate more of the work hardening effect after the first cold rolling.
[0100] Fig. 9 This is the metallographic structure after the third electric pulse treatment in the preparation process of the alloy of comparative example 6 of the present invention. Since the effective current density of the high-energy electric pulse is too high, the annealing temperature is too high. Even if the annealing time is short, the high-temperature coarsening rate of the grains driven by the electric effect is still very fast, and the average grain size is about 49.5 μm, which fails to provide favorable conditions for a fine and uniform grain structure for subsequent processing.
[0101] It can be seen from Example 1, Example 2 and Comparative Examples 1, 2, 3, 4, 5, 6 and 7 that the Cu-Fe alloy material prepared by the present invention has the characteristics of high hardness, high strength, high conductivity and high softening temperature; there is a synergistic effect between the various steps and the various condition parameters in the present invention. When a certain parameter or a certain process link is not within the protection scope of the present invention, the performance of the resulting product is far worse than that of the present invention.
[0102] It should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solutions of the present invention may be modified or replaced by equivalents without departing from the spirit and scope of the technical solutions of the present invention, which should all be included in the scope of the claims of the present invention.
Claims
1. A Cu-Fe alloy material having high strength, high conductivity and high heat resistance, characterized in that: The Cu-Fe alloy material has the following composition, in mass percentage: Fe: 0.8-3%, Mg: 0.05-0.2%, Si: 0-0.1%, Nb: 0-0.2%, V: 0-0.1%, P: 0-0.1%, and the balance is Cu. Meanwhile, the total mass percentage of Si, V, P, and Nb is less than 0.2%.
2. The Cu-Fe alloy material having high strength, high conductivity and high heat resistance according to claim 1, characterized in that: The Cu-Fe alloy material has the following composition, in percentage by mass: Fe: 1.5-3%, Mg: 0.05-0.15%, Si: 0-0.05%, Nb: 0-0.05%, V: 0-0.05%, P: 0-0.05%, and the balance is Cu.
3. A method for preparing a Cu-Fe alloy material having high strength, high conductivity and high heat resistance as claimed in claim 1 or 2, characterized in that: An ingot is obtained by smelting, and the ingot is subjected to a first electric pulse treatment; then hot rolling is performed, and after hot rolling, a second electric pulse treatment is performed, and after the second electric pulse treatment, a first cold rolling treatment, a third electric pulse treatment, a second cold rolling treatment are performed in sequence, and a fourth electric pulse treatment is performed to obtain a Cu-Fe alloy material; the cooling method after the first electric pulse treatment, hot rolling, and the second electric pulse treatment is water quenching.
4. The method for preparing a Cu-Fe alloy material having high strength, high conductivity and high heat resistance according to claim 3, characterized in that: The smelting process is as follows: pure copper, Cu-Fe master alloy, Cu-V master alloy, Cu-Nb master alloy, pure Si, pure Mg and pure P are prepared according to the designed proportion, pure copper is first melted, then the temperature is raised to 1200-1300° C., Cu-Fe master alloy is added in 2-3 batches, the mixture is kept warm for 2-3 minutes and then stirred for 30-60 seconds, then Cu-V master alloy, Cu-Nb master alloy, pure Si, pure Mg and pure P are added, the mixture is kept warm for 1-2 minutes, the mixture is cooled down to 1150-1250° C. while stirring, and then casting is performed.
5. The method for preparing a Cu-Fe alloy material having high strength, high conductivity and high heat resistance according to claim 3, characterized in that: The parameters of the first electric pulse treatment are: frequency of 3000-5000 Hz, pulse width of 500-3000 μs, and current density of 4000-8000 A / mm 2 , effective current density is 550~2500 A / mm 2 The maximum temperature of the first electric pulse treatment is 750-950°C, and the time of the first electric pulse treatment is 2-5 min.
6. The method for preparing a Cu-Fe alloy material having high strength, high conductivity and high heat resistance according to claim 3, characterized in that: The hot rolling process is to first keep the temperature at 850-950°C for 0.5-1 h, then hot roll, control the deformation of a single pass of hot rolling to be 20-40%, the total deformation to be 50-90%, and the total number of passes to be ≤3; The thickness of the hot-rolled billet obtained after the hot rolling is ≥10 mm.
7. The method for preparing a Cu-Fe alloy material having high strength, high conductivity and high heat resistance according to claim 3, characterized in that: The parameters of the second electric pulse treatment are: frequency of 2000-5000 Hz, pulse width of 500-3000 μs, and current density of 3000-8000 A / mm 2 , effective current density is 500~2000 A / mm 2 The maximum temperature of the second electric pulse treatment is 700-900°C, and the time of the second electric pulse treatment is 20 s-5 min.
8. The method for preparing a Cu-Fe alloy material having high strength, high conductivity and high heat resistance according to claim 3, characterized in that: The deformation of a single cold rolling pass is 10-20%, the total deformation is 50-90%, and the number of passes is ≤6; The thickness of the blank obtained after the first cold rolling is ≥1 mm.
9. The method for preparing a Cu-Fe alloy material having high strength, high conductivity and high heat resistance according to claim 3, characterized in that: The parameters of the third electric pulse treatment are: frequency of 2000-5000 Hz, pulse width of 500-3000 μs, and current density of 1500-5000 A / mm 2 , effective current density is 500~1500 A / mm 2 ; The temperature of the third electric pulse treatment is 550-650°C, and the time of the third electric pulse treatment is 20 s-60 s; The single deformation amount of the secondary cold rolling is 10-15%, the total deformation amount is 50-90%, and the total number of passes is ≤7.
10. The method for preparing a Cu-Fe alloy material having high strength, high conductivity and high heat resistance according to claim 3, characterized in that: The parameters of the fourth electric pulse treatment are: frequency of 2000-4000 Hz, pulse width of 500-3000 μs, and current density of 1500-4000 A / mm 2 , effective current density is 500~1200 A / mm 2 ; The temperature range of the fourth electric pulse treatment is 400-500°C, and the time of the fourth electric pulse treatment is 20 s-60s.
Citation Information
Patent Citations
Copper-iron alloy wire rod and preparation method thereof
CN110396619A
Preparation method of high-strength and high-corrosion-resistance Cu-Ni-Mn alloy
CN111004936A
Preparation method of ultrahigh-strength elastic copper alloy material
CN118222950A
Copper alloy having bendability and stress relaxation property
CN1793394A
Powder-metallurgical products and the production thereof
GB1298944A